2013
DOI: 10.1016/j.jaging.2013.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Coming together and pulling apart: Exploring the influence of functional status on co-resident relationships in assisted living

Abstract: Social relationships can have considerable influence on physical and mental well-being in later life, particularly for those in long-term care settings such as assisted living (AL). Research set in AL suggests that other residents are among the most available social contacts and that co-resident relationships can affect life satisfaction, quality of life, and well-being. Functional status is a major factor influencing relationships, yet AL research has not studied in-depth or systematically considered the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Further, decline in the health of AL residents affects their relationships and interactions in daily life, and is a cause of isolation, separation from others, loneliness, and more severe manifestations of depression. 5 , 37 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, decline in the health of AL residents affects their relationships and interactions in daily life, and is a cause of isolation, separation from others, loneliness, and more severe manifestations of depression. 5 , 37 …”
Section: Discussionmentioning
confidence: 99%
“…The best practice inside the AL environment has been reported to emphasize on the ability of staff to recognize signs of depression and make early interventions, for which training is essential. 37 Previous research has found that residents in assisted care facilities suffering from depressive symptoms experience frustration with their careers’ limited abilities to effectively deal with depression. 9 , 45 Therefore, an interdisciplinary approach to raise awareness among staff for early recognition of the symptoms of depression among AL residents is recommended.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Highlands transitioned from supportive to intolerant for cognitively impaired Mrs. Russell. This scenario, including shunning and social distancing, particularly in response to cognitive impairment and other frailties, affects all residents (Sandhu et al, 2013). Yet, couples' linked lives means the treatment of one affects both.…”
Section: Discussionmentioning
confidence: 99%
“…Reflecting the dynamism of relationships, residents engage in the process of "negotiating social careers in AL." Careers begin with the move and are negotiated over time, vary in content and nature, and are influenced by multilevel factors, including individual factors, such as functional status (see also Sandhu et al, 2013). Residents with spouses, siblings, or romantic partners have "built-in companionship."…”
mentioning
confidence: 99%